Army size, military recruitment and financing in Portugal during the period of the Peninsula War - 1808-1811 - Costa,Fernando Dores (2008)
This article is intended to offer a preliminary approach to some questions that were of central importance in the period of the so-called Napoleonic invasions in Portugal: the size of the army that was effectively raised, the difficulties that were encountered in recruiting men to serve in the ranks of this army, and finally the shortage of funds to finance the efforts to sustain this force. This is not an account of the Peninsular War on Portuguese territory, but makes some contributions to the renewal of the study of this period, namely through the use of quantitative sources.²